Food-related parenting practices and child and adolescent weight and weight-related behaviors. (March 2014) - A Loth, Katie; Fulkerson, Jayne A; Neumark-Sztainer, Dianne R
The prevalence of obesity and overweight in children has reached a concerning plateau in the past three decades, with overweight or obesity impacting approximately a third of youth. Unhealthy weight-related behaviors, such as dieting, skipping meals, fasting and binge eating, are also a great public health concern for young people given both their high prevalence and harmful consequences. Food-related parenting practices, including food restriction and pressure-to-eat, have been associated with higher weight status, as well as the use of unhealthy weight-related behaviors, in children and adolescents. Physicians and other healthcare providers who work with families should discourage parents from using food restriction and pressure-to-eat parenting practices with their child or adolescent. Alternatively, parents should be empowered to promote healthy eating by focusing on making nutritious food items readily available within their home and modeling healthy food choices for their child or adolescent.